Molecular Defects in Cardiac Myofilament Ca2+-Regulation Due to Cardiomyopathy-Linked Mutations Can Be Reversed by Small Molecules Binding to Troponin - Sheehan, Alice; Messer, Andrew E.; Papadaki, Maria; Choudhry, Afnan; Kren, Vladimír; Biedermann, David; Blagg, Brian; Khandelwal, Anuj; Marston, Steven B. (Frontiers in Physiology, 2018)
The inherited cardiomyopathies, hypertrophic cardiomyopathy (HCM) and dilated cardiomyopathy (DCM) are relatively common, potentially life-threatening and currently untreatable. Mutations are often in the contractile proteins of cardiac muscle and cause abnormal Ca2+ regulation via troponin. HCM is usually linked to higher myofilament Ca2+-sensitivity whilst in both HCM and DCM mutant tissue there is often an uncoupling of the relationship between troponin I (TnI) phosphorylation by PKA and modulation of myofilament Ca2+-sensitivity, essential for normal responses to adrenaline. The adrenergic response is blunted, and this may predispose the heart to failure under stress. At present there are no compounds or interventions that can prevent or treat sarcomeric cardiomyopathies. There is a need for novel therapies that act at a more fundamental level to affect the disease process. We demonstrated that epigallocatechin-3 gallate (EGCG) was found to be capable of restoring the coupled relationship between Ca2+-sensitivity and TnI phosphorylation in mutant thin filaments to normal in vitro, independent of the mutation (15 mutations tested). We have labelled this property “re-coupling”. The action of EGCG in vitro to reverse the abnormality caused by myopathic mutations would appear to be an ideal pharmaceutical profile for treatment of inherited HCM and DCM but EGCG is known to be promiscuous in vivo and is thus unsuitable as therapeutic drug. We therefore investigated whether other structurally related compounds can re-couple myofilaments without these off-target effects. We used the quantitative in vitro motility assay to screen 40 compounds, related to C-terminal Hsp90 inhibitors, and found 23 that can re-couple mutant myofilaments. There is no correlation between re-couplers and Hsp90 inhibitors. The Ca2+-sensitivity shift due to TnI phosphorylation was restored to 2.2±0.01 –fold (n=19) compared to 2.0±.24 fold (n=7) in wild-type thin filaments. Many of these compounds were either pure re-couplers or pure desensitisers, indicating these properties are independent; moreover, re-coupling ability could be lost with small changes of compound structure, indicating the possibility of specificity. Small molecules that can re-couple may have therapeutic potential.